Post-discharge pharmacological treatment discontinuation of forensic psychiatric patients in Sweden - Noland, Ebba; Virtanen, Suvi; Klötz Logan, Fia; Chang, Zheng; Strandh, Mattias (Frontiers in Psychiatry, 2024)
Most forensic psychiatric patients have chronic psychiatric disorders that require longterm pharmacological treatment even after discharge from care. However, the prevalence and correlates of post-discharge medication discontinuation in this patient group remain unclear.Objective: To investigate the prevalence and correlates of post-discharge discontinuation of pharmacological treatment in forensic psychiatric patients in Sweden.Methods: Data on individuals discharged from forensic psychiatric care between 2009 and 2018 (n =1142) with ongoing pharmacological treatment at the time of discharge (n =856) were identified from the Swedish National Forensic Psychiatric Register. Cox regression models were used to estimate the association between patient characteristics and medication discontinuation.Results: Of the 856 individuals with pharmacological treatment at discharge, 488 (57%) discontinued treatment within 2 years of discharge. Factors associated with an increased risk of treatment discontinuation varied between different types of psychotropic medications: the most important correlate was comorbidity between psychosis and personality disorder. Higher age at discharge, longer length of stay, having a history of several psychiatric care episodes, having a trustee, a limited guardian, and a supported living accommodation at the time of discharge were associated with a decreased rate of medication discontinuation. This applied for antipsychotics, antidepressants, antiepileptics and for any psychotropic medication, but not for psychostimulants or drugs used in addictive disorders.Conclusions: For many former forensic psychiatric patients, there are situational factors associated with medication discontinuation. This insight holds significance for professionals who are involved in pre-discharge planning within forensic psychiatric care and those who interact with this cohort of former patients post-discharge.